Modelling the Number of Stunting Under-Five Children in East Nusa Tenggara Using Negative Binomial Regression - Honesty Citra Mar’ati; Dian Lestari; Fevi Novkaniza (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Malnutrition is an imbalance in a person's energy intake or nutrition. Stunting is one of the nutritional problems in toddlers, where stunting is a condition of growth failure in children under five caused by malnutrition. In Indonesia, East Nusa Tenggara Province has the highest number of toddlers with stunting cases. Therefore, efforts are needed to reduce the number of stunting, especially in East Nusa Tenggara. Several factors are thought to be closely related to the high number of stunting in toddlers. This study aims to find factors that can significantly explain stunting in East Nusa Tenggara to help accelerate the decrease in the number of stunting. This study will explore stunting data from the Ministry of Home Affairs in 2021 for data on East Nusa Tenggara and the Central Statistics Agency of East Nusa Tenggara Province. The appropriate modelling for the number of stunting is the Poisson regression model because the number of stunting is in the form of count data. The proper modelling for stunting cases in toddlers is the Poisson regression model because stunting cases in toddlers are in the form of count data. There is an overdispersion problem to overcome overdispersion in the Poisson regression model; a more suitable Poisson regression model is used as an alternative model. Furthermore, the Maximum Likelihood Estimation (MLE) method estimates the model's parameters. The results showed that the complete immunization variable, pregnant women get nutritional counselling variable, the variable low birth weight babies and the variable of families with beneficiary status had a significant effect on the number of stunting in East Nusa Tenggara.